Concentration of heavy metals and rare earth elements in patients with brain tumours: Analysis in tumour tissue, non-tumour tissue, and blood. Issue 7 (3rd October 2021) - Gaman, Laura; Radoi, Mugurel Petrinel; Delia, Corina Elena; Luzardo, Octavio P.; Zumbado, Manuel; Rodríguez-Hernández, Ángel; Stoian, Irina; Gilca, Marilena; Boada, Luis D.; Henríquez-Hernández, Luis Alberto
ABSTRACT: Inorganic elements have been associated with brain tumours for long. The blood concentration of 47 elements was assessed by ICP-MS in 26 brain tumour patients and 21 healthy subjects from Bucharest (Romania). All 47 elements were detected in the brain tumour tissue, and 22 were detected in > 80% of samples; this implies that these elements can cross the blood-brain barrier. Median blood levels of cadmium, lead, and nickel were higher than the reference values (1.14, 53.3, and 2.53 ng/mL). Gadolinium and tantalum showed significantly higher concentrations among cases. We observed considerable differences and different profiles of the presence of inorganic elements between the tumour and non-tumour brain tissue and between tissue from the primary tumour and tissue from brain metastasis. Our data suggest that similar to heavy metals, other elements – commonly used in high tech devices and rare earth elements – can also influence brain tumour.